2017
DOI: 10.3238/arztebl.2017.0313
|View full text |Cite
|
Sign up to set email alerts
|

Coma After Acute Head Injury

Abstract: Brain tissue can tolerate ischemia and elevated pressure only for a very limited time. Comatose head-injured patients must therefore be evaluated urgently to determine whether they can be helped by the surgical removal of a hematoma or by a decompressive hemicraniectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 40 publications
0
10
0
4
Order By: Relevance
“…Figure 1a in the article (or the corresponding clinical course: epidural hematoma, operated 3 hours after the crash) shows that even here, the primarily presumed herniation of brainstem and cerebellar tonsils has not led to lasting injury even 3 hours after the event, such as was documented in the other case (Figure 1c), where the hematoma had obviously been drained much later (3). It always should be borne in mind, however, that epidural hemorrhages can develop slowly and gradually.…”
Section: Tissue Pressure and Perfusionmentioning
confidence: 96%
See 2 more Smart Citations
“…Figure 1a in the article (or the corresponding clinical course: epidural hematoma, operated 3 hours after the crash) shows that even here, the primarily presumed herniation of brainstem and cerebellar tonsils has not led to lasting injury even 3 hours after the event, such as was documented in the other case (Figure 1c), where the hematoma had obviously been drained much later (3). It always should be borne in mind, however, that epidural hemorrhages can develop slowly and gradually.…”
Section: Tissue Pressure and Perfusionmentioning
confidence: 96%
“…It suggests that acute head injury often affects young motorcyclists who are willing to take risks. Newer studies have found, however, that patients' age has risen continuously over recent years, and that, meanwhile, falls have taken over from traffic accidents as the most common causes of acute head injury (2,3). Although claims have been made to the contrary, over the past two decades no reduction in mortality due to acute head injury has been observed, and neither have outcomes improved to any significant degree (2).…”
Section: Falls Are More Common Than Traffic Crashesmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Prognose nach einem SHT korreliert signifikant mit den Faktoren ▪ Alter, ▪ Dauer der Bewusstlosigkeit, ▪ neurologische Begleitsymptomen und ▪ Lokalisation der Hirnschädigung [1].…”
Section: Prognoseunclassified
“…Bei Patienten unter 15 Jahren mit einem schweren SHT wird ein besseres Outcome erreicht als bei Erwachsenen [1].…”
Section: Prognoseunclassified